Impact of process and physico-chemical conditions on the formation of curcumin-whey protein composite particles capable to stabilize food-compatible oil in water emulsions. (January 2022) - Nayak, Aditya; Genot, Claude; Meynier, Anne; Dorlando, Angélina; Capron, Isabelle
Abstract: Use of nanonized curcumin-whey protein (CWP) composite particles as Pickering stabilizers are an attractive strategy due to their edibility and natural origin. This study aimed to examine the effect of physico-chemical conditions (pH, ionic strength, protein form) during the formation of CWP composite nanoparticles on their physico-chemical characteristics (size, surface charge, morphology) and further their Pickering ability by influencing their aptitude to stabilize oil/water interfaces. Our study demonstrated that, to favor the protein-curcumin interactions and to improve the particle characteristics (smaller size, monodispersity), one should increase the accessibility of hydrophobic moiety of proteins (denaturation) and control ionic strength. Increasing the concentration of the CWP composite nanoparticles decreased size and polydispersity enhancing emulsion stability. Use of these CWP composite nanoparticles in food products with high ionic strength will tend to flocculation and thereby emulsions destabilization. This work allows for a better understanding of the role of physico-chemical conditions on the formation of CWP composite nanoparticles and thereof their oil/water interfacial activity. Highlights: Curcumin-whey protein (CWP) composite particles were fabricated by nanonization. Effect of ionic strength, pH, heat treatment on CWP composite particle was studied. Whey protein denaturation enhanced protein-curcumin interaction. Fluorescence spectroscopy allowed studying the interaction between protein and curcumin. CWP composite particles stabilized oil-in-water Pickering emulsions.